A Kinesiological analysis of piano technique as employed in selections of György Cziffra’s piano transcriptions - Fick, Cornelis Uys Lourens (Stellenbosch : Stellenbosch University, 2019)
Thesis (MPhil)--Stellenbosch University, 2019.